Answer:
3x>12 2x/3 ≤ 6
3x>12, x = 4 2x/3, x = 2 ≤ 6
Answer:
-66
Step-by-step explanation:
-(-2)^2=-4
-3(-2)(-3)+2(-3)^3= -62
-4-62= -66
Answer:
a < -1
Step-by-step explanation:
Okay, so we are given this equation:
t(x) = ax^5 + 2
Lets plug in -2 as x and see what happens.. t(x) can be 66..
= 66
-32a + 2 = 66
-32a = 64
a = -2
A is less than -1,
a < -1
Answer:
Check explanation
Step-by-step explanation:
I'll give you my way of solving it and you can figure it out from there.
<CEA = <DEB due to vertical angles
AE = ED due to midpoint theorem
<CAD = <ADB due to alternating angles theorem
thus two triangles congruent due to ASA
Answer:
48
Step-by-step explanation: